A ciência, a pós-graduação em biotecnologia e o percurso profissional - Pereira, Thaís Almeida (2019)
Through the postgraduate course Brazil has sought to consolidate its scientific base and the training of qualified human resources to solve regional and national problems. The adequacy between the level and type of academic training and the professional situation has been a very present topic of debate. In general, the fate of masters and doctors graduated by the Brazilian postgraduate is a subject with possibility and necessity of exploration. The area of Biotechnology is considered as a strategic area for development and pointed as a priority for growth, in terms of the creation of new Masters and PhD courses. We did not detect studies with graduates in this area. This thesis sought to analyze, through a case study, the repercussions of the Postgraduate in Biotechnology for the professional life of masters and doctors who graduated in the period from 2013 to 2016 in a program that has a level of excellence according to the last evaluation carried out by Capes. In order to achieve this goal, the following areas were analyzed: the Biotechnology area, taking into account its conception, application areas, strategic area, philosophical paradigm and Capes evaluation area; analysis of the context of the evolution of the Policies of Science, Technology and Innovation, of Science, of Post- Graduation and of the formation and insertion of masters of doctors in Brazil; state of the art of studies on postgraduate students stricto sensu; identification of graduates, at an academic master's and doctorate level, graduated from 2013 to 2016; identification of the profile and the professional destination and the perception of the repercussions of the training on the part of the graduates. The information obtained in the Curriculum Lattes, the application of questionnaires and interviews were used. Content analysis of the questionnaire responses and the interviews was done by thematic analysis. The analysis of content in profiles of graduates, motivations for entry into the postgraduate course, competences and attributes, life and professional insertion, and satisfaction with work and training were divided. As the most relevant findings it can be highlighted that there is a description of greater difficulties of professional insertion in recent years. Among the employees, most of the survey participants reported some kind of professional improvement upon completion of the course. For the majority there was increase in the remuneration and opportunity of professional improvement after the masters and / or doctorate. The main motivations that led them to graduate are to contribute to science and provide a better paid career. Regarding job satisfaction and relationships with colleagues and boss, they are satisfied and have good relationships. The remuneration and benefits of the position are considered as regular. The data reveal that the professional insertion of the personnel object of this research is occurring in a diversified way. This study shows evidence, but it is a research that is closely linked to the oscillations of the labor market. However, the country's need to develop a national development project that is capable of understanding science, technology and innovation as a nation project is clear.